(untitled) (Fiep Bulletin - online, 2011)
This article addresses the uniqueness and regionality of the wheel and play nursery rhymes related to teaching and curriculum of folk culture and a strong interest in children, which were developed with children 01 to 05 years of Municipal Unit for Early Childhood Education Pratinha years 2009 and 2010, designs and circuits of that institution. The goal was to enhance games and nursery rhymes sung and danced by the children in addition to carrying more playful promoting educational values of local culture, children’s culture and higher amplitude of the overall development of children regardless of age, through the playfulness, expressions,dances and joys. As relevant aspects of this action, we believe that playing with wheels sung has a privileged place in children’s culture because it reveals wide incursion of the child with oral language, bodily, musical, gestural, and many possibilities to create new moves to learn. It is also a source of research with the family that brings a lot of reading and learning that customary law is passed on from father to son when he played the streets, squares and / or yards of turnstiles and toys sung, however, still need to be more valued as social practices. Therefore, our findings show that teaching the rich universe of wheels sung, the children’s games are inexhaustible sources of play and different languages in the curriculum of early childhood education.